Analysing the history of British social welfare : compassion, coercion and beyond - Parker, Jonathan, 1960- (Policy Press, 2023)
This book offers insights into the development of social welfare policies in Britain. By identifying continuities in welfare policy, practice and thought throughout history, it offers the potential for the development of new thinking, policy making and practice.